Case Report: Whipple’s disease pneumonia caused by inhalation of gas or liquid - Sun, Xiaokui; Zhu, Huizhi (Frontiers in Medicine, 2025)
Tropheryma whipplei (T. whipplei) is a Gram-positive bacterium that causes rare clinical infections, which primarily manifest as gastrointestinal infections and, more rarely, pulmonary diseases. Furthermore, immunosuppression is considered a predominant risk factor for T. whipplei infection. Several studies have indicated an association between T. whipplei infection and immunocompromised conditions; however, a few studies have also revealed that aspiration may be a potential predisposing factor for T. whipplei-related aspiration pneumonia. This case study reports two different cases of aspiration-induced T. whipplei pneumonia, each exhibiting unique clinical manifestations, imaging features, and therapeutic responses. Both patients had a history of aspiration, and their diagnoses were confirmed via mNGS. They were treated with sulfamethoxazole–trimethoprim (SMZ), which effectively alleviated the symptoms of mild T. whipplei pneumonia. However, in one case, the patient suffered from a severe co-infection of T. whipplei and Aspergillus following a drowning incident, which was effectively treated with meropenem and voriconazole co-therapy. This study provides novel data on T. whipplei infection and improves clinical awareness of aspiration-related pneumonia.